Revisiting the concentration-discharge (C-Q) relationships with high-frequency measurements - Tunqui Neira, José Manuel (2019)
Descargue el texto completo en el repositorio institucional de la Sorbonne Université: https://tel.archives-ouvertes.fr/tel-03282322